Improving diesel engine performance with hydrogen-fumigated soapnut biodiesel - Christopher Selvam D; Yuvarajan Devarajan; Aditya Kishore Dash; Shivendu Saxena; Beemkumar Nagappan; Vinod Kumar Singh; Prabhukumar Sellamuthu (Results in Engineering, 2025)
The pursuit of sustainable and economically viable alternatives to diesel fuel has catalyzed increased scholarly attention towards biodiesel produced from non-edible biomass, particularly Soapnut fruit biodiesel (SFB). Notwithstanding its ecological advantages, SFB is accompanied by increased emissions of nitrogen oxides (NOx) and a reduction in engine efficiency. This investigation examines the ramifications of hydrogen fumigation on the combustion efficiency and emission characteristics of a single-cylinder compression ignition (CI) engine operating on SFB. Hydrogen was administered at 10 % of the intake air volume, a parameter determined through preliminary optimization experiments. Empirical assessments conducted under five distinct engine load scenarios (0–100 %) demonstrated a 6.0 % enhancement in brake thermal efficiency (BTE) and a 7.1 % decrease in brake-specific fuel consumption (BSFC) when utilizing SFB in conjunction with hydrogen (SFB + H₂) compared to SFB utilized in isolation. Emission analyses revealed significant reductions of 12.1 % in NOx, 40.2 % in carbon monoxide (CO), and 30.4 % in smoke opacity. Furthermore, hydrocarbon (HC) emissions were reduced by 33.3 %, while peak in-cylinder pressure increased by 10.3 %, and the heat release rate (HRR) improved by 20.0 %. These enhancements can be attributed to the superior diffusivity, rapid flame propagation, and minimal ignition energy associated with hydrogen, which facilitate a more thorough combustion process. The findings substantiate the viability of hydrogen-enhanced SFB as a promising dual-fuel strategy for achieving cleaner and more efficient engine performance in various domains, including agriculture and transportation.